Elementos traço em água e sedimento na bacia hidrográfica do Rio Santa Maria da Vitória (ES) - Salles, Roberta Chechetto (2018)
The population growth leads to an increase in activities related to urbanization and industrialization, which are responsible for increasing trace elements in water sources. These elements present significant toxicity, and may accumulate over decades in the environment, generating risks to human health and ecosystem. In this sense, it is necessary to quantify trace elements in order to evaluate the contamination of the environment and its effects. In this context, this work aims to quantify and evaluate the contamination by trace elements: Fe, Mn, Ni, As, Cd, Cu, Co andPbin samples of water, surface sediment and of the corein the watershed of the river Santa Maria da Vitória. The river basin Santa Maria da Vitória is located in the central region of the Espírito Santo occupying an area of 1.563,3 km2. It is born in the mountain region of the state and includes the municipalities of Santa Maria de Jetibá and Santa Leopoldina, and part of the municipalities of Cariacica, Serra, Vila Velha, Viana and Vitória. In its middle course it suffers two buses, of the reservoirs Rio Bonito and Suíça. Two campaigns were carried out in march and november 2016. In these campaigns, samples of water and surface sediment were collected from the Santa Maria da Vitória river (5 stations) and Rio Bonito (3 stations), Suíça(2 stations) and Duas Bocas (3 stations). In the reservoir, the water samples were collected on the surface and at different depths and in the second campaign, in addition to the water and surface sediment samples, a sediment sample was collected in each of these reservoir. The analytical methodology was evaluated for sensitivity and linearity, accuracy and limits of detection and quantification.The water samples were filtered, acidified and analyzed by ICP-MS for the Mn, Ni, As, Cd, Cu, Co, and Pb elements and by ICP OES for Fe. Sediment, surface and sample samples were digested in and analyzed by ICP-MS for the Ni, As, Cd, Cu, Co and Pb elements and by ICP OES for Fe and Mn. The results obtained for the Santa Mariada Vitória river show the great impact that the stream São Luiz has been suffering through the dumping of different types of tailings from different origins. The results for the water samples and surface sediment of the dams indicate the difference between the river, intermediate and lacustrine zones. By means of the concentration of the trace elements and the dating(Pb210)of the sediment samples from the Rio Bonito reservoir, Suíça and Duas Bocas, an association was made with the historical events occurring at each site.To better interpret the data, the enrichment factor and the PLI and IR pollution parameters were analyzed. In addition, the granulometry and mineralogy of the samples and Pearson's analysis were performed in order to assist in the discussion of the results. The distribution of the elements in the soil is governed by interactions between the elements themselves and the same with attributes such as clay and silt fractions and Fe and Mn oxides, in addition to interaction with organic matter.The studies also indicate that Rio Bonito is in an alert situation, due to the large amount of tailings that are retained in this reservoir, from the rural and industrial activities of Santa Maria Jetibá. The maintenanceof the Suíça reservoir caused a change in the sediment column, compromising the results of this study. Whilefor Duas Bocas, it is clear that the results are a reflection of deforestation and the use of land for agriculturewhich occurred decades ago.